The Effects of a High-Intensity Ultrasound on the Fermentative Activity and Kinetic Growth of Lactobacillus Acidophilus and Lactobacillus Helveticus - Norma Angélica Bolívar-Jacobo; Raúl Alberto Reyes-Villagrana; Gerardo Pavel Espino-Solís; Ana Luisa Rentería-Monterrubio; Martha María Arévalos-Sánchez; Rogelio Sánchez-Vega; Eduardo Santellano-Estrada; David Chávez-Flores; América Chávez-Martínez (Fermentation, 2023)
An ultrasound, a non-thermal technique, can be employed to increase a probiotic’s biomass and its fermentation products. The effects of high-intensity ultrasounds (20%, 30%, and 40% amplitudes for 3 min) on the growth and fermentative profile of Lactobacillus acidophilus and helveticus were studied. The use of an ultrasound decreased the Lag phase and increased the maximum growth potential; however, the effect depended on the amplitude used. For both probiotics, the β-galactosidase activity increased in the treatments with a 20% amplitude—3 min and 30% amplitude—but decreased in the treatment with a 40% amplitude—3 min in comparison to the values found in the control treatment. The two probiotics showed a decrease in the protein concentration when compared with the control treatment. Both probiotics presented the lowest values of proteolysis in the treatments with a 30% amplitude—3 min. Lactic, acetic, and citric acids were the organic acids that were present in the highest concentration and formic acid was not detected in either of the two probiotics. It can be concluded that the ultrasound amplitude has a noticeable influence on the growth and fermentation profiles of both probiotics. The results from this study could be used in subsequences investigations to enhance the postbiotic production of Lactobacillus acidophilus and Lactobacillus helveticus.